Nanofabrication of sharp conductive diamond tip probe chips and their application in reverse tip sample scanning probe microscopy - L. Wouters; J. Cho; S. Gim; J. Yang; A. Kanniainen; K. Lee; P. Lagrain; N. Peric; T. Hantschel (Micro and Nano Engineering, 2025)
Recently, a new scanning probe microscopy (SPM) concept called reverse tip sample scanning probe microscopy (RTS SPM) was introduced. Here, a sample is mounted at the end of a cantilever beam and scans over a tip that is integrated into an array of hundreds of SPM tips, overcoming one of the major limitations of the SPM technique, namely, the time-consuming and experiment-interrupting manual tip exchange step. However, to fully exploit this novel approach, a chip with an array of densely packed, nanometer-sharp, and durable SPM tips is essential. Therefore, we have developed a fabrication process to integrate such an array of sharp, high aspect ratio, doped diamond tips – referred to as hedgehog full diamond tip (HFDT) – into so-called probe chips, facilitating high-resolution SPM measurements and enabling rapid and seamless sample movement from one tip to another within the RTS SPM framework. An array of pyramidally shaped, doped diamond tips is fabricated through consecutive molding and diamond deposition steps. A supporting membrane is formed by metal deposition and electroplating, followed by selective underetching of the silicon substrate to release the tip array membrane and enable probe chip assembly. Finally, a self-patterned dry etching step is employed to generate multiple nanoscopic sharp tips on top of the base diamond pyramids. In this work, we present our developed and optimized probe chip technology and demonstrate its high electrical conductivity, robustness under high tip load force, and excellent spatial resolution, rendering it highly suitable for diverse electrical SPM measurement modes.